Pengaruh Financial Leverage dan Profitabilitas Terhadap Income Smoothing Dengan Kualitas Audit Sebagai Pemoderas - Rasinih, Rasinih; Munandar, Agus (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 11 No 1 (2016)DO - 10.24843/JIAB.2016.v11.i01.p05, 2016)
This study aimed to examine the effect of Financial Leverage and Profitability against income smoothing with Quality Audit as a moderating. Profitability measured by return on assets formula net income divided by total assets. Financial Leverage is measured by finding the ratio between total liabilities and total assets of a company. Meanwhile, with the smoothing Income Gain Flattening Index and Quality audits with dummy. The population in this study 134 company, with the period of 2011 until 2013, the Company analyzed 20 companies. The method of analysis used data from this study multiple regression analysis. But earlier, descriptive statistical analysis and classical assumption. Results of this study show variable financial leverage and profitability and significant influence on income smoothing. Keywords: Financial Leverage, profitability, income smoothing, quality audit
Keywords: Financial Leverage, profitability, income smoothing, Quality audit